The Impacts of Visual Aids in Promoting the Learning Processes in Schools in Pakistan - J. I., Hamad (African Journal of Education and Practice, 2023)
Purpose: The purpose of this study is to investigate the impacts of visual aids in promoting the learning processes in schools in Pakistan. Methodology: The study adopted a desktop methodology. Desk research refers to secondary data or that which can be collected without fieldwork. Desk research is basically involved in collecting data from existing resources hence it is often considered a low cost technique as compared to field research, as the main cost is involved in executive's time, telephone charges and directories. Thus, the study relied on already published studies, reports and statistics. This secondary data was easily accessed through the online journals and library. Findings: The findings of the study revealed the existence of a contextual and methodological gap relating to the impacts of visual aids in promoting the learning processes in schools. Preliminary empirical review found that using visual aids as a teaching aid stimulates thinking and improves the learning environment in the classroom. Effective use of visual aids substitutes monotonous learning environments. Students develop and increase personal understanding of the areas of learning when they experience a successful and pleasant learning in the classroom. Students find visual aids sessions useful and relevant when it has some direct relation to the course content. Unique Contribution to Theory, Practice and Policy: The Cognitive Load Theory may be used to anchor future studies on the impacts of visual aids in promoting the learning processes in schools in Pakistan. Schools and their administration must share the opinions of the students regarding the use of visual aids that will be helpful in enhancing the learning process. Refresher courses, workshops and conferences may be arranged for the teachers for improving their skills of using audio visuals to the needs of the students. There is need for the Ministry of Education to mount periodic training sessions for teachers who are already in the field to be retrained on recent discovery regarding the use of teaching/learning resources.